“I’m a paper and pencil person”: a qualitative descriptive study of potential barriers and facilitators to engagement with pre-operative total knee replacement education and prehabilitation digital interventions - Anna M. Anderson; Anthony C. Redmond; Judith Joseph; Gretl A. McHugh (BMC Musculoskeletal Disorders)
Abstract Background Interest in using digital interventions to provide pre-operative total knee replacement (TKR) education and prehabilitation (health/wellbeing optimization) support is growing. Patient engagement with digital interventions tends to be poor; therefore, exploring the intended users’ perspectives during digital intervention development is vital. This study was part of a project focused on developing a pre-operative TKR education and prehabilitation digital intervention, the ‘Virtual Knee School’ (VKS), and aimed to explore patients’ perspectives of potential barriers/facilitators to engagement with the VKS to inform its development. Methods This United Kingdom-based, qualitative descriptive study involved 14 purposively selected patients who were awaiting/had undergone TKR. Three online focus groups were conducted to explore patients’ perspectives of barriers and facilitators to engagement with the behaviors targeted by the VKS and digital features that could address the barriers/facilitators. The focus groups were audio-recorded, professionally transcribed, and analyzed inductively using reflexive thematic analysis. Three Patient and Public Involvement representatives were involved in aspects such as reviewing the recruitment materials and/or plain English summary of the study findings. Results Two intersecting themes were developed. Theme 1, ‘Accounting for individual differences’, suggests pre-operative TKR digital interventions should account for the impact of individual differences on engagement with digital technologies, pre-operative education and prehabilitation. Most participants felt a pre-operative TKR digital intervention would be valuable; however, a couple of older participants appeared reluctant to use digital technologies. Participants’ perspectives of specific digital features and pre-operative TKR education and prehabilitation also varied widely. Theme 2, ‘Tailoring to the pre-operative context’ highlights the importance of tailoring pre-operative TKR digital interventions to pre-operative contextual features, including physiological/psychological factors, social/occupational factors and limitations in pre-operative TKR care provision. Various digital features that could address these factors were identified. Conclusions This study’s findings suggest pre-operative TKR digital interventions should account for individual differences and be tailored to the pre-operative TKR context. Given that some patients are reluctant to use digital technologies, also offering pre-operative TKR support in non-digital formats is essential. The findings have been used to inform a VKS prototype and could also be used to inform the development of other pre-operative TKR digital interventions.